008 Demonstration of cardiac AL amyloidosis regression after succesful chemotherapy. a CMR study. (3rd April 2017) - Martinez-Naharro, Ana; Abdel-Gadir, Amna; Treibel, Thomas A; Zumbo, Giulia; Knight, Daniel S; Rosmini, Stefania; Lane, RN Thirusha; Mahmood, Shameem; Sachchithanantham, Sajitha; Whelan, Carol J; Lachmann, Helen J; Wechalekar, Ashutosh D; et al.
Abstract : Background: Cardiac involvement in immunoglobulin light chain (AL) amyloidosis is the major determinant of survival; Cardiac response to chemotherapy is conventionally assessed by serum brain natriuretic peptide (NT-proBNP) and echocardiography, but neither quantify amyloid burden. The aim of this study was to evaluate cardiac AL amyloid serially using cardiovascular MR (CMR) including extracellular volume measurement (ECV), which is the site of the amyloid deposits. Methods: 31 patients with cardiac AL amyloidosis who had chemotherapy were studied serially using ECG, echocardiography, 123 I-labelled serum amyloid P component (SAP) scintigraphy, NT-proBNP measurements and CMR with T1 mapping and ECV measurements (mean interval 20±11 months). Nineteen patients achieved a complete or very good partial haematological response (CR n=10; VGPR n=9). Twelve patients attained a partial response (PR) or no response (NR). Results: At follow-up (mean 20±11 months), the amyloid burden had decreased substantially in 6 of the 10 (60%) attaining a CR, 6 of the 9 (67%) in VGPR and 1 of the 8 (13%) in PR. Changes in the ECV consistent with regression of amyloid were concordant with the changes in native T1, reduction in amyloid volume and in 5 patients with changes in late gadolinium enhancement pattern (figure 1 ). Overall there was significant reduction in NT-proBNP concentration, LV mass, left atrial area and improvement in diastolic function in patients whose amyloid burden decreased. Regression of cardiac amyloid by CMR correlated with regression of amyloid in other organs measured by SAP scintigraphy.